PENGEMBANGAN KAPASITAS ( CAPACITY BUILDING) KELEMBAGAAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN JEPARA - Hapsari, Adhela Mahda; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
In performing their duties and responsibilities, organizations are often faced with problems related to institutional capacity development. The Municipal Office for Disaster Prevention of Jepara Regency is necessary to make efforts in evaluating disasters. The office, including the providing facilities and infrastructure pursuant to the standards required by the National Office for Disaster Prevention (BNPB), such as adequate budgets and capable human resources. This descriptive-qualitative study aimed to find out the institutional capacity development of the municipal office for disaster prevention (BPBD) of Jepara Regency in preventing. The study found that the inistitutional capacity at BPBD of Jepara Regency had not been optimally developed due to lacking budgets, poor quality and limited human resources, and infrastructures as well as facilities. The study also found lacking participation of all staff in the decision-making process. The supporting factors of the institutional capacity development at the municipal office fore disaster prevention of Jepara Regency included mutual commitment between stakeholders to preventing disasters and environmental conservation. Whereas, the impending factors were staff resistance and legal procedures dealing with the disaster prevention efforts. The stud recommended public-private collaboration through corporate social responsibility programs as well as good cooperation and periodical coordination with concerned municipal working units